Evaluation of Immunostimulatory Effects of Bacterial Lysate Proteins on THP-1 Macrophages: Pro-inflammatory Cytokine Response and Proteomic Profiling - Md. Mijanur Rahman; Asma Talukder; Md. Sifat Rahi; Plabon Kumar Das; I. Darren Grice; Glen C. Ulett; Ming Q. Wei (Journal of Immunology Research)
Bacterial lysate proteins (BLPs) serve as potential immunostimulants, recognized by pattern recognition receptors (PRRs) on immune cells, eliciting a robust immune response. In this study, THP-1 macrophages were treated with varying doses of BLPs derived from Streptococcus pyogenes (SP), Streptococcus agalactiae (SA), and Serratia marcescens (SM). The results showed significant increases (p <0.05) in pro-inflammatory cytokines such as TNF-α, IL-1β, IL-6, IL-12, granulocyte macrophage-colony stimulating factor (GM-CSF), eotaxin, and macrophage inflammatory protein (MIP)-1α, except for 5 µg of all BLPs for TNF-α and eotaxin, and 5 µg of SP for IL-12 production. No significant differences were found between the corresponding doses of SP and SA or SP and SM, except for GM-CSF in all doses, while SA and SM only showed a difference at the 5 µg dose for GM-CSF. Furthermore, there were no significant differences between the 10 and 20 µg doses of all BLPs, indicating that doses higher than 10 µg do not significantly enhance the pro-inflammatory response. Combination doses of SP + SM and SA + SM did not show significant differences, except for IL-1β, suggesting no synergistic effect. Cytotoxicity was observed to increase with higher BLP concentrations in a dose-dependent manner, with combinations of SP + SM and SA + SM exhibiting greater cytotoxicity than the individual BLPs. Proteomic analysis of BLPs identified immunostimulatory proteins, including heat shock proteins (HSPs; ClpB, DnaK, and GroEL), metabolic enzymes (glyceraldehyde 3-phosphate dehydrogenase (GAPDH), enolase, and arginine deiminase (ADI)), and surface and secreted proteins (ESAT-6-like protein, CRISPR-associated endonuclease Cas9, OmpA, porin OmpC, and serralysin), which are involved in immune modulation, bacterial clearance, and immune evasion. This study underscores the potential of bacterial proteins as vaccine adjuvants or supplementary therapies; however, further research is essential to find a balance between immune activation and inflammation reduction to develop safer and more effective immunostimulants.